Analisis Perilaku Masyarakat Menghemat Energi Listrik dan Beberapa Faktor yang Mempengaruhi Pada Rumah Tinggal Tipe Kecil di Kabupaten Polman Sulawesi Barat - Sugeng A Karim; Faizal Amir; Muhammad Ardi; Alimuddin Sa’ban Miru (Seminar Nasional LP2M UNM, 2022)
Summary. The objectives of this study are as follows: (1) to determine the behavior of the community to save electrical energy in small type houses in Polman Regency, (2) to determine the knowledge of electrical energy, local wisdom, and the attitude of the community to save electrical energy who inhabit small type houses in Polman Regency, (3) to determine the effect of electrical energy knowledge, local wisdom, and community attitudes to save electrical energy, both individually and collectively on community behavior in saving electrical energy in small type houses in Polman Regency. This research is classified as correlational research. The research is located in Polman Regency. The population of this study is the community (head of household) who live in small type houses in Polman Regency. The sample area is Wonomulio District selected by purposive sampling method. Respondents (sample) are 50 heads of families who live in small type houses that already use electrical energy. The research variables consist of: (1) the dependent variable (Y), and (2) the independent variable (X). The dependent variable is community behavior in saving electrical energy (Y). The independent variables are: (a) knowledge of electrical energy (X1); (b) local wisdom (X2); and (c) attitude to save electrical energy (X3). The data analysis techniques used are: (1) Descriptive statistical analysis, (2) Inferential statistical analysis. The analytical models used are: (1) simple regression analysis and (2) multiple regression analysis. The results of the study are as follows: (1) Community behavior in saving electrical energy in small type houses in Polmant Regency is in the high category, (2) knowledge of electrical energy, local wisdom of the community who live in small type houses in Polman Regency is in the low category, while the attitude of saving electrical energy is in the high category, (3) knowledge of electrical energy, local wisdom, and the attitude of saving electrical energy, both individually and collectively affect the behavior of the community to save electrical energy in small type houses in Polman Regency.  Keywords: Knowledge, Behavior, Attitude, Local Wisdom, Electrical Energy